Genotoxická agens v lidské stravĕ - Srb, V (Ceskoslovenske zdravotnictvi, 1990)
Food is characterized as one of the basic factors of the living environment of the human population and human health as the highest criterium of quality of these factors. Attention is paid above all to genotoxic agents in food in particular to mutagens and carcinogens which are formed during thermal treatment. The author makes the Czechoslovak professional public familiar with the pilot study of Hatch et al. of 1988 (13) which provides a list of 1007 references from the world literature on the possible genotoxicity of thermally treated food. The list is open and can be supplemented in the Lawrence National Laboratory in Livermore (USA) where it is at the same time available to everybody interested. Information is provided in "libget" software/rdb data base for the electronic computer system Unix. It is, however, also possible to obtain data from IBM PC(5.25") diskettes.
Keywords: vaření; Cooking; informační systémy; Information Systems; mutageny; Mutagens; analýza potravin; Food Analysis